Effect of betaine supplementation on cycling sprint performance - Pryor J Luke; Craig Stuart AS; Swensen Thomas (Taylor & Francis Group, 2012)
Abstract Purpose To examine the effect of betaine supplementation on cycling sprint performance. Methods Sixteen recreationally active subjects (7 females and 9 males) completed three sprint tests, each consisting of four 12 sec efforts against a resistance equal to 5.5% of body weight; efforts were separated by 2.5 min of cycling at zero resistance. Test one established baseline; test two and three were preceded by seven days of daily consumption of 591 ml of a carbohydrate-electrolyte beverage as a placebo or a carbohydrate-electrolyte beverage containing 0.42% betaine (approximately 2.5 grams of betaine a day); half the beverage was consumed in the morning and the other half in the afternoon. We used a double blind random order cross-over design; there was a 3 wk washout between trials two and three. Average and maximum peak and mean power were analyzed with one-way repeated measures ANOVA and, where indicated, a Student Newman-Keuls. Results Compared to baseline, betaine ingestion increased average peak power (6.4%; p < 0.001), maximum peak power (5.7%; p < 0.001), average mean power (5.4%; p = 0.004), and maximum mean power (4.4%; p = 0.004) for all subjects combined. Compared to placebo, betaine ingestion significantly increased average peak power (3.4%; p = 0.026), maximum peak power max (3.8%; p = 0.007), average mean power (3.3%; p = 0.034), and maximum mean power (3.5%; p = 0.011) for all subjects combined. There were no differences between the placebo and baseline trials. Conclusions One week of betaine ingestion improved cycling sprint power in recreationally active males and females.